2020
DOI: 10.1080/13506285.2020.1825141
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical distinction between functional states in working memory and their corresponding neural states

Abstract: Working memory (WM) is important for guiding behaviour, but not always for the next possible action. Here we define a WM item that is currently relevant for guiding behaviour as the functionally "active" item; whereas items maintained in WM, but not immediately relevant to behaviour, are defined as functionally "latent". Traditional neurophysiological theories of WM proposed that content is maintained via persistent neural activity (e.g., stable attractors); however, more recent theories have highlighted the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 107 publications
(136 reference statements)
1
45
0
Order By: Relevance
“…Despite apparent similarities, TMS perturbations impact working memory performance [5,6,[42][43][44], while pinging does not [7,45] (see also chapter 4 of [46]). This suggested that these approaches could be interacting with fundamentally different neural mechanisms [7,47]. Indeed, we found through the reanalysis of the data of [6]…”
Section: Differential Mechanisms For Pinging-and Tms-induced Reactivationsmentioning
confidence: 78%
“…Despite apparent similarities, TMS perturbations impact working memory performance [5,6,[42][43][44], while pinging does not [7,45] (see also chapter 4 of [46]). This suggested that these approaches could be interacting with fundamentally different neural mechanisms [7,47]. Indeed, we found through the reanalysis of the data of [6]…”
Section: Differential Mechanisms For Pinging-and Tms-induced Reactivationsmentioning
confidence: 78%
“…Some have interpreted these results as consistent with the idea that whereas prioritized memory items (PMI) are held in an active state, UMIs may be maintained as “activity-silent” traces encoded in synaptic weights (Barak & Tsodyks, 2014; Stokes, 2015). Although this possibility remains a topic of vigorous debate (Christophel et al, 2018; Schneegans & Bays, 2017; Sprague et al, 2016; Stokes et al, 2020), the present report does not relate directly to this question. Instead, of primary relevance here are more recent empirical results suggesting that, rather than producing a decline to baseline, deprioritization may produce a representational transformation of an item into a different, but still active, format.…”
Section: Introductionmentioning
confidence: 58%
“…For example, Cowan (1995Cowan ( , 2005 proposed that representations stored in the passive state (also called the activated part of LTM) are likely to be forgotten due to decay over time and interference (e.g., perceptual interference, interference from other cognitive processes, and competition among memory representations). However, some researchers have proposed that memory representations in the passive state could be protected from decay and shielded from interaction with the current task to minimize interference from the currently prioritized cognition or activity-based representations (de Vries et al, 2020;Muhle-Karbe et al, 2021;Stokes, 2015;Stokes et al, 2020). Thus, the passive state could be regarded as being protective, preventing information loss of the VWM representations.…”
mentioning
confidence: 99%